{Anorexia nervosa: A psychiatric illness with gynecological manifestations. A survey of knowledge and practice among Greek gynecologists} - Michala, L.; Antsaklis, A. (European Journal of Obstetrics Gynecology and Reproductive Biology, 2010)
Objective: Anorexia nervosa (AN) affects a large number of women, usually in their adolescence. One of the primary manifestations of the disease is menstrual irregularity, and the presence of a menstrual cycle is often used as a sign of recovery among patients. Women with AN are likely to seek medical advice from a gynecologist with regards to their period problems. The role of the gynecologist is therefore crucial in identifying and referring these patients promptly to specialised centers. Study design: A brief anonymous questionnaire was completed by 94 gynecologists practising in Athens. Results: Approximately half of the responders felt that the conditions were rarer than it really is, and 25{%} thought that the disease primarily affects women in their early twenties. Although 56{%} of gynecologists would not prescribe the combined oral contraceptive in women with AN in order to restore their periods, the remainder of gynecologists were in favour of prescribing hormone replacement with a view to reducing the risk of osteopenia. This is despite the fact that emerging evidence shows there is no benefit. Ten percent of gynecologists never weigh their patients during evaluation of amenorrhoea and 72{%} felt that their level of knowledge as far as anorexia nervosa is concerned is inadequate. Conclusion: More education is required among gynecologists on the subject of anorexia nervosa, in order to identify and refer patients in the early stages of the disease process. © 2010 Elsevier Ireland Ltd.
Keywords: Anorexia nervosa; Hormone Replacement Therapy; Hypothalamic amenorrhea; Osteopenia; Survey